2017
DOI: 10.23956/ijarcsse/sv7i5/0250
|View full text |Cite
|
Sign up to set email alerts
|

E-Commerce and Online Payment in the Modern Era

Abstract: Abstract-Face-to-face exchange of goods between the two sides conducted before the beginning of recorded history. Always there are some security problems in traditional payment system. After that electronics payments system brought out a huge revolution. Though modern technology digital documents can be copied perfectly, duplicate signature of anybody is possible. Name of the Buyer's can be linked with each payment, to eliminate the secrecy of money. Without proper and high-quality security system somehow e-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
(8 reference statements)
0
21
0
Order By: Relevance
“…Business models in e-commerce have phenomena in blockchain technology and collaborative economy [2] that impact collaboration connectivity between business actors such as multiplying peer-to-peer, peer-to-organization, and organization-to-peer exchanges [1]. Electronic Payment System (EPS) with data sharing is generally used through the application programming interface (API) by banks or fintech companies [3] and has been widely provided in line with e-commerce services [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Business models in e-commerce have phenomena in blockchain technology and collaborative economy [2] that impact collaboration connectivity between business actors such as multiplying peer-to-peer, peer-to-organization, and organization-to-peer exchanges [1]. Electronic Payment System (EPS) with data sharing is generally used through the application programming interface (API) by banks or fintech companies [3] and has been widely provided in line with e-commerce services [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…The positive association between online transactions and mobile money ownership remains consistent whether looked at in the OIC overall or by national income group. This finding indicates that in line with the tremendous growth of e-commerce, consumers can utilize aspects of mobile money services to make online transaction and simplify their transactions (Demirgüç-Kunt et al, 2018;Jenkins, 2008;Mukherjee & Roy, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…The development of e-commerce encourages consumers to use digital financial services (Mukherjee & Roy, 2017) so that mobile money usage can increase access and affordability for the making of payments (Jenkins, 2008). Empirical research conducted by Hasnain (2017) found a mutually beneficial association between e-commerce development and the increased adoption of mobile money.…”
Section: Previous Studiesmentioning
confidence: 99%
“…A cashless payment system is one that uses electronic means to make payments. It was not designed to replace currency, but rather to be a superior alternative to cash and trade barter [3]. With the rising usage of smartphones and internet accessibility, digital payment is rapidly replacing conventional wallets.…”
Section: Page 681mentioning
confidence: 99%
“…[2] The study agenda focuses on UPI as a retail payment digital payment platform, guaranteeing a clear picture of its usage pattern among the target population. [3] The comprehensive analysis includes both the key stakeholders' customers and merchants who are UPI end users. [4] The proposal is ready to assist policymakers in developing policies for the country's digital payment mechanism.…”
Section: Swoc Analysis Of Research Agendasmentioning
confidence: 99%